COMPARISON OF EGG QUALITY CHARACTERISTICS OF INDIGENOUS AND BROILER PARENT LINE CROSSED WITH INDIGENOUS CHICKEN - Pathak, SS; Barua, N; Kalita, N (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A comparative Study on egg characteristics of four type of indigenous chicken based on plumage pattern and a crossbred, (PB-2 x indigenous) was carried out . In the present study a total of 75 eggs, 15 eggs from each group were included. Out of five egg qualities, egg weight , shape index shell thickness ,yolk index and albumen index, except shape index, four characteristics were found significantly higher in group V(PB-2 x indigenous eggs); only shape index value of indigenous chicken groups were higher than the group V. The results of the present study indicated that the egg quality characteristic for crossed chicken (broiler parent line X indigenous chicken) is superior to indigenous chickens. Among indigenous chicken groups, group II (black with brown hackle) plumage colour pattern eggs were found to be higher for egg quality characteristics parameters.